2017
DOI: 10.1016/j.amjmed.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Squamous Cell Skin Carcinoma: A Game Changer?

Abstract: A 74-year-old white male was diagnosed with squamous cell carcinoma in 2013. Six months after Mohs surgery, he underwent a left superficial parotidectomy, left neck dissection, and excision of the left postauricular lymph node after confirmation of lymphatic spread. Pathology from the left parietal scalp lesion revealed multifocal invasive squamous cell carcinoma. Extranodal tumor extension was noted in a postauricular lymph node and left parotid gland, and he was diagnosed with stage IV squamous cell carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Recently, reports of six patients have demonstrated tumor regression of treatment-refractory cutaneous SCC specifically affecting the pre- and post-auricular and temporal regions with nivolumab as well as pembrolizumab, another PD-1 antibody [ 15 , 16 , 17 , 18 , 19 ]. Similar to nivolumab, pembrolizumab exerts its effect by interrupting the pathway that disarms T lymphocytes, preventing the immune-mediated destruction of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, reports of six patients have demonstrated tumor regression of treatment-refractory cutaneous SCC specifically affecting the pre- and post-auricular and temporal regions with nivolumab as well as pembrolizumab, another PD-1 antibody [ 15 , 16 , 17 , 18 , 19 ]. Similar to nivolumab, pembrolizumab exerts its effect by interrupting the pathway that disarms T lymphocytes, preventing the immune-mediated destruction of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to nivolumab, pembrolizumab exerts its effect by interrupting the pathway that disarms T lymphocytes, preventing the immune-mediated destruction of tumor cells. Review of the literature revealed 12 cases of locally advanced or metastatic SCC treated with nivolumab or pembrolizumab [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. An ongoing clinical trial (NCT02964559) is examining pembrolizumab as a primary treatment for locally advanced or metastatic SCC of the skin [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…108 A number of series have documented the efficacy of checkpoint inhibition for recurrent and metastatic cutaneous SCC, and one trial reported a response rate of approximately 50%. 106,[109][110][111] Numerous trials are underway to clarify the role of immunotherapy in the management of cutaneous SCC postoperatively and in the recurrent and metastatic settings. Case reports of the safety of hedgehog inhibitors with radiation for BCC have also been reported, and 2 such compounds are approved by the U.S. Food and Drug Administration for use in BCC that cannot be treated definitively.…”
Section: Systemic Therapymentioning
confidence: 99%
“…Recommended doses are 3 mg for kilograms of weight every 3 weeks as intravenous (iv) infusion for a period of 30 minutes. Among the different PD-1 inhibitors, the number of patients treated is the widest, about 28 reported in the literature (Assam et al, 2016;Borradori et al, 2016;Chang et al, 2016;Degache et al, 2018;Deinlein et al, 2017;Ferrarotto, 2017;Lipson et al, 2016;Ravulapati et al, 2017;Stevenson et al, 2017;Tran et al, 2017;Winkler et al, 2017;Zalaudek et al, 2019), excluding the ongoing trials in Phase I and II (Licitra et al, 2017;Kudchadkar et al, 2018;Maubec et al, 2019). Although the larger number of reported cases, responses data are not enough and in addition with short period of follow-up.…”
Section: Pembrolizumabmentioning
confidence: 99%